1990
DOI: 10.1007/bf01537420
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine augments hepatic regenerative response in rats

Abstract: A number of mechanisms participate in the hepatic injury that occurs during and following liver transplantation. A normal allograft regenerative response is probably essential for a successful transplant outcome. In this study, the effect of cyclosporine, a potent immunosuppressant used routinely after liver transplantation, on the regenerative response of the liver after partial hepatectomy was investigated. Male Wistar rats were pretreated for one week with either cyclosporine or the olive oil vehicle and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
2

Year Published

1991
1991
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 16 publications
2
22
0
2
Order By: Relevance
“…Interestingly, despite its recognized potential for intrinsic hepatotoxicity (1-10), CsA has been shown to have "hepatotrophic" effects after partial hepatectomy (11)(12)(13)(14)(15)(16) or a PCS (21). Furthermore, CsA does not appear to either prevent or limit the hepatic regenerative response observed when a small-for-size liver is transplanted into a larger recipient (29) or when a reduced-size liver is used in pediatric recipients (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, despite its recognized potential for intrinsic hepatotoxicity (1-10), CsA has been shown to have "hepatotrophic" effects after partial hepatectomy (11)(12)(13)(14)(15)(16) or a PCS (21). Furthermore, CsA does not appear to either prevent or limit the hepatic regenerative response observed when a small-for-size liver is transplanted into a larger recipient (29) or when a reduced-size liver is used in pediatric recipients (30).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic regeneration may be crucial during and immediately after transplantation, when the liver recovers from the injury experienced during the period of ischemic cold preservation and reperfusion. The acute effects of CsA on liver regeneration have been investigated recently by several different groups (11)(12)(13)(14)(15)(16). These studies have shown that CsA may actually enhance the hepatocyte's regenerative response after partial hepatectomy.…”
mentioning
confidence: 99%
“…120,121 Comparison of low-dose cyclosporine A (0.06 to 0.6 mg/kg/d) with low-dose tacrolimus (0.01 to 0.06 mg/kg/d) directly infused into the portal vein under partially ischemic conditions showed no difference in hepatotropic properties. 121 However, when greater doses of cyclosporine A (4 mg/kg/d) are compared, significantly greater mitosis is stimulated by high-dose tacrolimus (1 mg/kg/d).…”
Section: Hepatotropic Effects (Tissue Regeneration)mentioning
confidence: 99%
“…Attempts to prevent or to diminish the allograft injury associated with organ harvesting, reperfusion and rejection have already involved the use of several different pharmacological agents. Recently, experimental studies obtained in animals have focused considerable attention on the hepatotrophic activities of cyclosporin A (9)(10)(11)(12)(13)(14) and FK (2,3,15), two potent immunosuppressive agents currently being used after clinical OLT.…”
Section: Discussionmentioning
confidence: 99%